Highly sensitive micro-hygrometer based on microfiber knot resonator - Tian, Qin; Yang, Hang Zhou; Rong, Qiang Zhou; Feng, Zhong Yao; Wang, Ruo Hui; Zaini, Muhammad Khairol Annuar; Lim, Kok Sing; Ahmad, Harith; Zhang, Pan; Ding, Xiang Zi; Lu, Kai; He, Yu Dong (Elsevier, 2019)
In this work, we experimentally demonstrated a microfiber knot resonator (MKR) for ambient relative humidity (RH) measurement. The microfiber device was manufactured by forming a ring from a low-loss microfiber, fabricated from a single-mode fiber (SMF) by using flame-heating technique. The resonator was successfully formed when a periodic output resonance spectrum was achieved. Without employing any coating hygroscopic material, the MKR was observed to highly sensitive to the variation of ambient RH ranging from of 30% RH to 94% RH. The proposed device is an extremely compact and fast response sensor, useful for a wide spectrum of industrial applications.